A Novel Gas Extraction Technique in Coal Seams Utilizing Hydraulic Fracturing‐Dissolution and Analysis of Non‐Uniform Propagation of Fracture - Yun Lei; Yang Ju; Yongxiang Zheng; Xinze Peng (Energy Science & Engineering)
ABSTRACT Extracting gas from low‐permeability coal seams is essential for mine safety and efficiency. To address this challenge, a novel technique combining hydraulic fracturing and dissolution was proposed. The feasibility of this method was verified through simulations based on the distinct element method. Subsequently, the impact of weakened mechanical properties (deformation and strength) on fracture propagation was analyzed. Finally, the possibility of controlling the non‐uniform propagation of fractures through treatment parameters was discussed. The results indicate that fractures tend to preferentially expand in weakened zones when deformation parameters or strength parameters deteriorate. Greater degradation of deformation and strength leads to larger fracture offset. The degree of fracture offset can be reduced by increasing the viscosity of fracturing fluid, based on which manual control of fracture offset can be realized. This study introduces a hybrid method combining physical and chemical actions for coal seam gas extraction, offering theoretical guidance for practical applications.